Taxonomy of Atopsyche Banks (Trichoptera: Hydrobiosidae) from Brazil: New species, distributional notes and identification key - Gomes, Victor; Calor, Adolfo Ricardo (Zootaxa, 2016)
Three new species of Atopsyche Banks 1905 are described and illustrated from Brazil: Atopsyche diamantina n. sp., A. kamakan n. sp., and A. muelleri n. sp. New records of A. apurimac Schmid 1989, A. sanctipauli Flint 1974, A. serica Ross 1953, and A. zernyi Flint 1974 are included, as well as the first records to states of Bahia, Goiás, and Rio Grande do Sul. Atopsche rinconi Holzenthal & Cressa 2002 is recorded from Brazil for the first time. An identification key is also provided for species of the genus from Brazil. Moreover additional characters and illustrations of A. sanctipauli and A. zernyi are presented.